Being blind (or not) to scenarios used in sacrificial dilemmas: the influence of factual and contextual information on moral responses - Carron, Robin; Brigaud, Emmanuelle; Anders, Royce; Blanc, Nathalie (Frontiers in Psychology, 2024)
Introduction Traditionally, human morality has been largely studied with classical sacrificial dilemmas. A way to advance current understandings of moral judgment and decision-making may involve testing the impact of contexts that are made available to individuals presented with these archetypal dilemmas. This preliminary study focused on assessing whether the availability of factual and contextual information delivered through classical scenarios would change moral responses. Method A total of 334 participants were presented with sacrificial dilemmas either with a scenario or without a scenario before performing two moral tasks: one consisted in moral judgment (e.g., is it acceptable to sacrifice one person to save five?) and one was related to choice of action (e.g., would you sacrifice one person to save five?). In the condition with a scenario, participants were presented with a story describing the dilemma, its protagonists, their roles, the location and some background details of the situation, before answering to the two moral tasks. In the condition without a scenario, participants were only asked to perform the two moral tasks without any additional contextual elements usually provided by the scenario. Participants’ emotions were also measured before and after completing the two moral tasks. Results The results indicated that the presence of a scenario did not affect moral judgments. However, the presence of a scenario significantly increased utilitarian action choices (i.e., sacrificing one person in the interest of saving a greater number) and this effect was partially mediated by an increase in the perceived plausibility of the sacrificial action. Regarding emotional reaction to dilemmas, no differences were observed between the two conditions, suggesting that emotions are mainly based on the two moral tasks. Discussion These findings underscore the value of carefully considering the role of factual and contextual information provided by the scenarios in moral dilemmas.